THE RELATION BETWEEN SELF-EFFICACY TOWARD MATH WITH THE MATH COMMUNICATION COMPETENCE - Sylvia Rahmi; Rifka Nadia; Bibih Hasibah; Wahyu Hidayat (Jurnal Infinity, 2017)
The aim of this research is to analyze the relationship between self-efficacy toward mathematics with mathematical communication competence. The design of this research is survey and correlation technique. The research instruments used in this research are math communication competence test and attitude scale. The instruments used are 5 questions about math communication competenca teat and 28 statements about self-efficacy. The research population is all student of SMP Negeri 1 Soreang. With samples of this research were 70 students of 7th grade student chosen by cluster random sampling. The data analyzed quantitatively done through math communication data and self-efficacy attitude scale. SPSS 20 used in this research. The result shows that student self-efficacy influences students math communication competence.